2010
DOI: 10.1143/jjap.49.072101
|View full text |Cite
|
Sign up to set email alerts
|

Design of the Ring Remote Phosphor Structure for Phosphor-Converted White-Light-Emitting Diodes

Abstract: A phosphor-converted light-emitting diode structure with an increased phosphor extraction efficiency owing to the ring remote phosphor structure achieves a maximum luminous efficacy of 145 lm/W at 20 mA and a maximum luminous flux of 132 lm at 400 mA. The ring remote phosphor structure consists of an inverted cone lens encapsulant and a surrounding ring remote phosphor layer. Ray-tracing simulations demonstrate that the phosphor extraction efficiency of the ring remote phosphor structure exceeds 93%. A high ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…The ordinary two-step molding process was used to fabricate the ring-remote-phosphor layer around the central encapsulant [14], [15]. The inverted-cone-lens surface of the encapsulant was formed using a cylindrical cavity mold with a conical prominence at the bottom following the LED chip mounted on heat sink and wiring.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ordinary two-step molding process was used to fabricate the ring-remote-phosphor layer around the central encapsulant [14], [15]. The inverted-cone-lens surface of the encapsulant was formed using a cylindrical cavity mold with a conical prominence at the bottom following the LED chip mounted on heat sink and wiring.…”
Section: Resultsmentioning
confidence: 99%
“…In 2009, our research group demonstrated the ringremote-phosphor structure for pcLEDs [14], [15]. The ringremote-phosphor structure consists of an inverted-cone-lens encapsulant and a surrounding ring-remote-phosphor layer.…”
Section: Inverted-cone-lens Encapsulant With Gradientmentioning
confidence: 99%
“…For encapsulants with intermediate refractive indices, θ c increases and ultimately LEE increases. There have been many studies of encapsulants addressing modification of the shape of the encapsulation [14], addition of particles into the encapsulant [15], the effects of the hardening characteristics of the encapsulant [16], the development of encapsulants with high refractive indices [17,18], and multilayered encapsulation [19]. Most of these studies have focused on spherical encapsulants, but because of the current trend of using high-power, multichip LED packages, the need to study flat encapsulants has arisen.…”
Section: )mentioning
confidence: 99%
“…To improve the extraction efficiency of the remote phosphor structure with low angular-dependent correlated color temperature (CCT) deviation, the phosphor structures with a textured surface or dual-layer phosphor, obtained using the pulse spray coating method, were used to increase the package efficiency and color uniformity [5]. The ring remote phosphor structure proposed by Lin et al consists of an inverted cone lens encapsulant; a surrounding ring remote phosphor layer was later developed [6][7][8]. The ring remote phosphor layer could increase the extraction of back-transferred light and enhance the luminous efficacy to a greater extent.…”
Section: Introductionmentioning
confidence: 99%